The stand for conducting acceptance tests of asynchronous electric machines by method of mutual loading - A. V. Bublik; V. V. Bublik; N. V. Yesin; D. A. Titanakov (Омский научный вестник)
Improving the reliability and increasing the operational life of electrical equipment of electric rolling stock is one of the eight directions of scientific and technical development of JSC «Russian Railways» described in the target program «Strategy for the development of railway transport in the Russian Federation until 2030», approved by the decree of the Government of the Russian Federation. The solution to the problem of improving operational reliability is associated with comprehensive measures that include a wide range of issues aimed at ensuring the stable operation of rolling stock and its systems. Reliable operation of electric machines, which depends on the quality of repairs, has a significant impact on the operational reliability of electric rolling stock.